PCR Detection of Viral Nucleic Acid in Fatal Asthma: Is the Lower Respiratory Tract a Reservoir for Common Viruses? - Vasilija Macek; Azzeddine Dakhama; James C Hogg; Francis HY Green; Bruce K Rubin; Richard G Hegele (Canadian Respiratory Journal)
BACKGROUND: There is indirect evidence implicating viral respiratory tract infections in the pathogenesis of fatal asthma. However, it is unknown whether viruses are present within the lower respiratory tract in fatal asthma.